Peran ATC Supervisor, ATC Checker dan OJTI Dalam Pelayanan Lalu Lintas Penerbangan diBandara Mopah Merauke - Atmia, Kurniaty (Politeknik Penerbangan Makassar, 2018)
Community needs for air transportation services showed a significant increase. This is based on the increasing growth of aircraft movements and the number of passengers and goods at the Mopah Merauke Airport. The author identifies some of the problems that occur as follows: At each service shift there is no supervisor who controls potential irregularities; The use of the Merauke Pratama Branch Office as a PLLU cadet / on the job training (OJT) location; ATC performance checks are carried out by ATC who are considered experienced. The author formulates the problem of the role of the ATC Supervisor, ATC Checker and OJTI according to the Civil Aviation Safety Regulations at the Mopah Merauke Airport. The results of the study indicate that it is necessary to appoint several personnel as supervisors to supervise Air Traffic Services. Also the provision of ATS checker education to Air Traffic Guidance officers for the implementation of Performance Check Rating, and the provision of education on the Job Training Instructor for ATC personnel.